PROBLEMATIQUE DE FACTEURS DETERMINANTS DE SANTE DES INDIVIDUS : CAS DU MARCHE DE L’INDUSTRIE AERONAUTIQUE DE TRANSPORT DE (IAT) A KISANGANI EN REPUBLIQUE DEMOCRATIQUE DU CONGO - Baelongandi , Augustin Sombo (IJRDO - Journal of Business Management, 2021)
The situation of the market of the IAT in the city of Kisangani in RDC with his various realities and activities pass for a fountain of fecal peril, notably with the presence of the garbage so much strong that liquids; the deficiency in drinking water, the insufficiency of the latrines as well as a dirtiness. It demonstrates the factors that determine the health of the individuals at the end of the investigating led to the basis to see to what level the sellers, the persons responsible of the IAT market and all authorities of the summit to the basis consider this curse.